Mechanical signals protect stem cell lineage selection, preserving the bone and muscle phenotypes in obesity. Issue 1 (11th September 2017) - Frechette, Danielle M.; Krishnamoorthy, Divya; Pamon, Tee; Chan, M. Ete; Patel, Vihitaben; Rubin, Clinton T.
Abstract: The incidence of obesity is rapidly rising, increasing morbidity and mortality rates worldwide. Associated comorbidities include type 2 diabetes, heart disease, fatty liver disease, and cancer. The impact of excess fat on musculoskeletal health is still unclear, although it is associated with increased fracture risk and a decline in muscular function. The complexity of obesity makes understanding the etiology of bone and muscle abnormalities difficult. Exercise is an effective and commonly prescribed nonpharmacological treatment option, but it can be difficult or unsafe for the frail, elderly, and morbidly obese. Exercise alternatives, such as low‐intensity vibration (LIV), have potential for improving musculoskeletal health, particularly in conditions with excess fat. LIV has been shown to influence bone marrow mesenchymal stem cell differentiation toward higher‐order tissues (i.e., bone) and away from fat. While the exact mechanisms are not fully understood, recent studies utilizing LIV both at the bench and in the clinic have demonstrated some efficacy. Here, we discuss the current literature investigating the effects of obesity on bone, muscle, and bone marrow and how exercise and LIV can be used as effective treatments for combating the negative effects in the presence of excess fat.